2019
DOI: 10.3167/nc.2019.140202
|View full text |Cite
|
Sign up to set email alerts
|

Anthropocene Dynamics in the Prehistoric Pacific

Abstract: How will human societies evolve in the face of the massive changes humans themselves are driving in the earth systems? Currently, few data exist with which to address this question. I argue that archaeological datasets from islands provide useful models for understanding long-term socioecological responses to large-scale environmental change, by virtue of their longitudinal dimension and their relative insulation from broader biophysical systems. Reviewing how colonizing humans initiated biological and physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…These anthropogenic processes and feedbacks are often captured under the term 'global change' (e.g., Sage 2020, Turner et al 1991. Even though industrial societies have had the greatest impact, even smaller scale preindustrial societies durably altered landscapes and their sustained influence can be found within the multifarious palaeoecological records (e.g., Dubois et al 2017, Leppard 2019.…”
Section: Socioecological Systems and Some Issues With Their Analysismentioning
confidence: 99%
“…These anthropogenic processes and feedbacks are often captured under the term 'global change' (e.g., Sage 2020, Turner et al 1991. Even though industrial societies have had the greatest impact, even smaller scale preindustrial societies durably altered landscapes and their sustained influence can be found within the multifarious palaeoecological records (e.g., Dubois et al 2017, Leppard 2019.…”
Section: Socioecological Systems and Some Issues With Their Analysismentioning
confidence: 99%